Coming to Terms with Lightness and Brightness: Effects of Stimulus Configuration and Instructions on Brightness and Lightness Judgments - Blakeslee, Barbara (2008)
To recover surface reflectance and illuminance from the raw luminance signal the visual system must use prior assumptions and strategies that make use of additional sources of information. Indeed, it has been found that depending on experimental conditions, lightness (apparent reflectance) may refer to judgments that are similar to brightness judgments (apparent luminance), that are similar to local brightness-contrast judgments, or that represent an independent third dimension of achromatic experience which exists only when the illumination across regions of the display is visibly non-uniform (Arend & Spehar, 1993a; b). This means that lightness data generated in one experimental condition may not be comparable to lightness data measured in other conditions. We investigate this problem with regard to a history of data on simultaneous brightness contrast by measuring brightness, brightness contrast and lightness in stimuli similar to those used in Gilchrist’s edge-substitution studies (Gilchrist, Delman & Jacobsen, 1983), and in stimuli similar to those used to test Gilchrist’s intrinsic-image model against his newer anchoring model (Gilchrist, 2006). Our results clarify confusions which appear to stem from comparing different types of lightness judgments and from inadvertently using brightness as an index of lightness under conditions where independent lightness judgments are possible.